3D Wettable Framework for Dendrite‐Free Alkali Metal Anodes. Issue 18 (9th May 2018) - Zhang, Ying; Wang, Chengwei; Pastel, Glenn; Kuang, Yudi; Xie, Hua; Li, Yiju; Liu, Boyang; Luo, Wei; Chen, Chaoji; Hu, Liangbing
Abstract: The infinite volume change and dendritic behavior in alkali metal anodes lead to low Coulombic efficiency and short‐circuit issues that significantly hamper renewed efforts at commercialization. Here, a dendrite‐free alkali metal anode, made by thermally preloading molten Li or Na into a 3D framework with high alkali wettability, is reported. In the mechanically robust 3D framework, carbon fiber (CF) serves as an electrical highway that provides fast charge transfer for the redox reaction. Through a facile solution‐based process, a SnO2 coating is introduced to modify the poor wetting behavior of the carbon framework and drastically improve both the electrochemical performance and reliability. The kinetic barrier to adhesion of molten alkali metals on the CF framework is eliminated by the mixed reaction with SnO2 . The growth of dendrites is effectively repressed under the decreased local current density of the 3D framework. In full‐cell configurations with LiFePO4 cathodes, the Li–CF electrode shows reduced polarization and 90% capacity retention after 500 cycles in traditional carbonate electrolyte. Comparable improvements are also observed in 3D electrodes for Na metal batteries. These findings on a stable 3D carbon framework with improved wetting behavior provide significant practical implications for achieving safe and commercially viable alkali metal anodes. Abstract : Stable alkali (Li or Na) anodes are designed by adopting a 3D Li/Na wettable framework. The kinetic barrier to adhesion of molten alkali metals on the carbon fibers' framework is eliminated by the mixed reaction with SnO2 . The 3D wettable framework builds an electrical highway, guides uniform nucleation, regulates local electrical field, and inhibits Li dendrites.